Taking the long view : a study of longitudinal documentary - Kilborn, R. W. (Book collections on Project MUSE., 2013)
Taking the Long View is a study of documentary series such as Michael Apted's world-famous Seven Up films that set out to trace the life-journeys of individuals from their earliest schooldays till they are fully grown adults, often with children of their own. In addition to Seven Up, the book provides extended accounts of the two other best known longitudinal series to have been produced in the last three or four decades: Winifred and Barbara Junge's The Children of Golzow and Swedish director Rainer Hartleb's The Children of Jordbrö. Long docs have been an especially popular form of documenta.